A Phase II trial of Higher RadiOtherapy Dose In The Eradication of early rectal cancer (APHRODITE): protocol for a multicentre, open-label randomised controlled trial. Issue 4 (28th April 2022) - Hudson, Eleanor M; Noutch, Samantha; Brown, Sarah; Adapala, Ravi; Bach, Simon P; Burnett, Carole; Burrage, Alwyn; Gilbert, Alexandra; Hawkins, Maria; Howard, Debra; Jefford, Monica; Kochhar, Rohit; et al.
Abstract : Introduction: The standard of care for patients with localised rectal cancer is radical surgery, often combined with preoperative neoadjuvant (chemo)radiotherapy. While oncologically effective, this treatment strategy is associated with operative mortality risks, significant morbidity and stoma formation. An alternative approach is chemoradiotherapy to try to achieve a sustained clinical complete response (cCR). This non-surgical management can be attractive, particularly for patients at high risk of surgical complications. Modern radiotherapy techniques allow increased treatment conformality, enabling increased radiation dose to the tumour while reducing dose to normal tissue. The objective of this trial is to assess if radiotherapy dose escalation increases the cCR rate, with acceptable toxicity, for treatment of patients with early rectal cancer unsuitable for radical surgery. Methods and analysis: APHRODITE (A Phase II trial of Higher RadiOtherapy Dose In The Eradication of early rectal cancer) is a multicentre, open-label randomised controlled phase II trial aiming to recruit 104 participants from 10 to 12 UK sites. Participants will be allocated with a 2:1 ratio of intervention:control. The intervention is escalated dose radiotherapy (62 Gy to primary tumour, 50.4 Gy to surrounding mesorectum in 28 fractions) using simultaneous integrated boost. The control arm will receive 50.4 Gy to the primary tumour and surrounding mesorectum. Both arms will use intensity-modulated radiotherapy and daily image guidance, combined with concurrent chemotherapy (capecitabine, 5-fluorouracil/leucovorin or omitted). The primary endpoint is the proportion of participants with cCR at 6 months after start of treatment. Secondary outcomes include early and late toxicities, time to stoma formation, overall survival and patient-reported outcomes (European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaires QLQ-C30 and QLQ-CR29, low anterior resection syndrome (LARS) questionnaire). Ethics and dissemination: The trial obtained ethical approval from North West Greater Manchester East Research Ethics Committee (reference number 19/NW/0565) and is funded by Yorkshire Cancer Research. The final trial results will be published in peer-reviewed journals and adhere to International Committee of Medical Journal Editors guidelines. Trial registration number: ISRCTN16158514 .